Higher anticholinergic drug scale (ADS) scores are associated with peripheral but not cognitive markers of cholinergic blockade. Cross sectional data from 21 Norwegian nursing homes. (5th February 2013) - Kersten, Hege; Molden, Espen; Willumsen, Tiril; Engedal, Knut; Wyller, Torgeir Bruun
<x xml:space="preserve">Abstract</x> Aim This study evaluated a presumed gradual decline in cognitive function in nursing home residents when the anticholinergic drug scale (ADS) score increased above 3. Method The study population was recruited from 21 nursing homes in Norway. Criteria for inclusion were ADS score ≥ 3 and no severe dementia, defined as Clinical Dementia Rating (CDR) score < 3. Primary cognitive end points were CERAD 10‐word lists for recall and Mini Mental State Examination (MMSE). Secondary end points were activity of daily living (ADL), mouth dryness and serum anticholinergic activity (SAA). The patients were stratified into subgroups according to ADS score, i.e. a reference group with score 3 and test groups with scores 4, 5 or ≥6. End points were compared by analyses of covariance (ancova). Results Overall, 230 of the 1101 screened nursing home residents (21%) had an ADS score ≥3. After exclusion 101 residents were recruited and among these, 87 managed to participate in the study. No significant differences were detected in cognitive function or ADL when ADS increased above 3 (P > 0.10), but in vivo (mouth dryness) and in vitro (SAA) measures of peripheral anticholinergic activity were significantly higher in patients with an ADS score ≥6 (P < 0.01). Conclusion The present study does not support a progressive decline in cognitive function with ADS score above 3. This might indicate that the ADS score model has limited potential to predict the clinical risk of central anticholinergic side effects in frail elderly patients receiving multiple anticholinergic drugs.